1992
DOI: 10.1093/treephys/10.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient distribution in 16-year-old maritime pine

Abstract: Concentrations and contents of the micronutrients Fe, Mn, Zn, Cu, and B were measured in various tree compartments of a 16-year-old stand of maritime pine (Pinus pinaster Soland in Ait.). The micronutrients were actively redistributed within the tree. The longer-lived aerial tissues, trunks and branches, constituted the major micronutrient reservoirs, with the exception of manganese which accumulated in the needles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
2
10
1
1
Order By: Relevance
“…The increased availability of nitrogen accelerated the turnover of this element throughout the system but not its accumulation in perennial organs. Unlike oak species [3,37,41,47,84], beech and other hardwood species do not exhibit differential storage and concentrations of nutrients in the different parts of the tree.…”
Section: Nitrogen Dynamicsmentioning
confidence: 99%
“…The increased availability of nitrogen accelerated the turnover of this element throughout the system but not its accumulation in perennial organs. Unlike oak species [3,37,41,47,84], beech and other hardwood species do not exhibit differential storage and concentrations of nutrients in the different parts of the tree.…”
Section: Nitrogen Dynamicsmentioning
confidence: 99%
“…The increased availability of N accelerated the turnover of this element throughout the system and not its accumulation in perennial organs. Beech and other hardwood species do not exhibit differential storage and concentrations of nutrients in the different parts of the tree, unlike oak species (Albert and Prescoller-Tiefenthaler, 1992;Helmisaari, 1992;Jokela et al, 1981;Lemoine et al, 1988;Saur et al, 1992).…”
Section: Leaf Litterfall and Return Of C And N To The Soilmentioning
confidence: 99%
“…In the present study with Scots pine the observed Mn concentration was in agreement with natural ranges in boreal stands on Ferric Podzols (Merilä and Derome 2008). Smaller Mn concentrations (123-297 mg kg −1 ), are found in needles of 33-year-old Scots pine on acidic, nutrient poor soil; in the 16-year-old maritime pine, and in needles of 50-80-year-old Scots pine in the relatively unpolluted area (Grønflaten et al 2005;Sauer et al 1992;Tervahattu et al 2001). Liming and base cation fertilisation of acidic forest soils did not cause significant reduction in the currentyear needle Mn concentration in 33-year-old Scots pine stand after 4 years (Grønflaten et al 2005).…”
Section: Mineral Elements In Needlesmentioning
confidence: 99%